EFEKTIVITAS MEDIA AR (AUGMENTED REALITY) TERHADAP KEMAMPUAN PENJUMLAHAN BILANGAN CACAH KELAS II SEKOLAH DASAR - Tri Andini Nurfadillah; Henry Aditia Rigianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the use of Augmented Reality (AR) media can help grade II elementary school students to be better able to add integers. The ability of augmented reality (AR) to clarify difficult ideas or concepts shows its potential for use in the classroom. Through interesting and dynamic visualizations, Augmented Reality (AR) helps learners understand abstract concepts, the object of this research is learning media, namely Augmented Reality media. The merging of digital components in real-time with real-world features is the basic concept of augmented reality (AR). The quasi-experimental research method is applied in a quantitative research approach. Nonequivalent Control Group Design is the research design used in this study. Normality test, homogeneity test, and independent t test are some of the data analysis techniques used. The results showed that as many as 25 students (89.2%) when learning by using augmented reality media produced posttest scores with the maximum value category > 80, as many as 19 students (67.8%) when learning by using book media produced posttest scores with the maximum value category > 80. This shows that learning with Augmented Reality (AR) is more effective than conventional learning. This shows that learning addition using Augmented Reality (AR) effectively improves the ability to add numbers in grade II SD.